2018
DOI: 10.14444/5072
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biomechanical Evaluation of a Novel, Minimally Invasive, Sacroiliac Joint Fixation Device

Abstract: Background: Sacroiliac (SI) joint pathology may result in low-back pain, which causes substantial disability. Treatment failure with operative management of SI pain may be related to incomplete fusion of the joint and to fixation failure. The objective of this study was to evaluate the initial biomechanical stability of SI joint fixation with a novel implantable device in an in vitro human cadaveric model. Methods: The right and left sides of 3 cadaveric L4-pelvis specimens were tested (1) intact, (2) destabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…In this study, after sacroiliac screw xation, the rotation angle of SIJ reduced by 48%, and the displacement of SIJ reduced by 57%. It could be seen that the ROM of SIJ signi cantly reduced, which was consistent with the previous studies 29,30 . The results suggested that sacroiliac screw xation was an effective method for SIJ xation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, after sacroiliac screw xation, the rotation angle of SIJ reduced by 48%, and the displacement of SIJ reduced by 57%. It could be seen that the ROM of SIJ signi cantly reduced, which was consistent with the previous studies 29,30 . The results suggested that sacroiliac screw xation was an effective method for SIJ xation.…”
Section: Discussionsupporting
confidence: 92%
“…In an in vitro study on seven human specimens, they found a reduction of the ROM of 41%, 36% and 36% in exion-extension, lateral bending and axial rotation, respectively. Cross et al 29 argued that under the torque of exion-extension, lateral exion, rotation, the rotation angles of SIJ were 2.92° and 1.75°, 1.16°a nd 0.59°, 1.46° and 1.52° in the state of intact SIJ and xed SIJ with sacroiliac screw. In this study, after sacroiliac screw xation, the rotation angle of SIJ reduced by 48%, and the displacement of SIJ reduced by 57%.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Previous in vitro biomechanical studies demonstrated that 3 triangular titanium implants placed across the sacroiliac joint significantly reduced range of motion (ROM) compared with that in the intact joint. [22][23][24] Multiple biomechanical studies have demonstrated that using 1 sacroiliac joint screw results in less stability than that achieved with the placement of 2 screws across the joint. [25][26][27][28] The general hypothesis-that increased number of fixation points across the sacroiliac joint improves stability-is corroborated by these studies; however, data are scarce about this effect in long-segment constructs used to address adult spinal deformity.…”
mentioning
confidence: 99%
“…Biomechanically, these implants reduce the SI joint range of motion (ROM) compared with the intact joint. [17][18][19][20][21][22][23][24][25] In a finite element modeling study, Lindsey et al 26 reported that ROM was sequentially reduced as the number of implants placed across the SI joint increased from 1 to 3. More broadly, multiple biomechanical studies have demonstrated that a single SI joint screw results in less stability than two screws across the joint.…”
mentioning
confidence: 99%